Polish Translation and Validation of the Tinnitus Handicap Inventory and the Tinnitus Functional Index - Wrzosek, Małgorzata; Szymiec, Eugeniusz; Klemens, Wiesława; Kotyło, Piotr; Schlee, Winfried; Modrzyńska, Małgorzata; Lang-Małecka, Agnieszka; Preis, Anna; Bulla, Jan (Frontiers in Psychology, 2016)
The need for validated measures enabling clinicians to classify tinnitus patients according to the severity of tinnitus and screen the progress of therapies in our country led us to the translation into Polish and the validation of two tinnitus questionnaires, namely the Tinnitus Handicap Inventory (THI) and the Tinnitus Functional Index (TFI). Design: The original English version of questionnaires were translated into Polish and translated back to English by three independent translators. These versions were then finalized by the authors into a Polish THI (THI-Pl) and a Polish TFI (TFI-Pl). Participants from three laryngological centers in Poland answered anonymously the THI-Pl (N=98) and the TFI-Pl (N=108) in addition to the Polish versions of the Center for Epidemiologic Studies Depression Scale (CES-D) as a measure of self-perceived level of depression, and the Satisfaction With Life Scale (SWLS) to assess self-perceived quality of life. Both were used to determine discriminant validity. Two Visual Analog Scales (VAS) were used to measure tinnitus annoyance and tinnitus loudness in order to determine convergent validity. Results: Similar to the original version of the THI, the THI-Pl showed a high internal consistency (Cronbach's alpha=0.93). The exploratory factor analysis revealed that the questionnaire has a three-factorial structure that does not correspond to the original division for functional, catastrophic and emotional subscales. Convergent and discriminant validity were confirmed. The TFI-Pl showed high internal consistency (Cronbach's alpha=0.96) with the reliability ranging from 0.82 to 0.95 for its different subscales. Factor analysis confirmed an eight-factorial structure with factors assigning all items to appropriate subscales reported in the original version of the questionnaire. Discriminant and convergent validity were also confirmed for the TFI-Pl. Conclusions: We translated and validated the Polish versions of the THI and the TFI to make it suitable for their clinical use in Poland.